Study on the Detectability of the Sky-Surface Wave Hybrid Radar - Hou Chengyu; Ke Guo; Shi Tiange; Wang Yuxin (Journal of Applied Mathematics)
Working in the HF (high-frequency) band and the transmitter and receiver locating separately, the sky-surface wave hybrid radar both has the capabilities of the OTHR (over-the-horizon radar) and the advantage of the bistatic radar. As the electromagnetic wave will be disturbed by the ionosphere, interfered by the sea clutter and attenuated by the sea surface, the detectability of this radar system is more complex. So, in this paper, we will discuss the problem detailedly. First of all, the radar equation is deduced based on the propagation of the electromagnetic wave. Then, how to calculate the effect of the ionosphere and the propagation loss is discussed. And an example based on the radar equation is given. At last, the ambiguity function is used to analyze the range and velocity resolution. From the result, we find that the resolution has relation with the location of the target and the height of reflection point of the ionosphere. But compared with the location, the effect of the ionospheric height can be ignored.